2014
DOI: 10.2147/clep.s73728
|View full text |Cite
|
Sign up to set email alerts
|

The Western Denmark Cardiac Computed Tomography Registry: a review and validation study

Abstract: BackgroundAs a subregistry to the Western Denmark Heart Registry (WDHR), the Western Denmark Cardiac Computed Tomography Registry (WDHR-CCTR) is a clinical database established in 2008 to monitor and improve the quality of cardiac computed tomography (CT) in Western Denmark.ObjectiveWe examined the content, data quality, and research potential of the WDHR-CCTR.MethodsWe retrieved 2008–2012 data to examine the 1) content; 2) completeness of procedure registration using the Danish National Patient Registry as re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…Only two studies have looked at diagnostic investigations. Nielsen et al7 found a completeness of registrations of coronary CT angiographies of 72% in the DNPR. In a report from the Danish Health and Medicines Authority from 2003, the completeness of the records of fetal umbilical artery flow velocity in the DNPR was 47% compared to the medical records 6.…”
Section: Discussionmentioning
confidence: 99%
“…Only two studies have looked at diagnostic investigations. Nielsen et al7 found a completeness of registrations of coronary CT angiographies of 72% in the DNPR. In a report from the Danish Health and Medicines Authority from 2003, the completeness of the records of fetal umbilical artery flow velocity in the DNPR was 47% compared to the medical records 6.…”
Section: Discussionmentioning
confidence: 99%
“…Results of the CCTA were blinded from the investigators until the cohort was established. Baseline information regarding traditional risk factors and demographic data were recorded from the validated database33 .…”
mentioning
confidence: 99%
“…The only previous study to examine the validity of cardiac examinations in the DNPR focused on 282 patients, on whom cardiac CT angiography was performed between 2008 and 2012 9. Using medical records as reference, this study found a PPV of 100% (95% CI 99% to 100%) for this examination 9.…”
Section: Discussionmentioning
confidence: 80%